DECONSTRUCTION AND THE DEATHS OF PHILOSOPHY: OF METAPHYSICS AND MOURNING FOR THE ARCHIVE - Trifonas, Peter (Surfaces, 2001)
Through a reading of Derrida, the author addresses questions concerning the "right" of philosophy's birth and death, and the ethics of its body of teaching. Taking into account Derrida's destruction of logocentrism, if any reaffirmation of "philosophy" as the interpretational moment of a disciplinary line of inquiry is to occur, it can only be through a responsible questioning of what is said and left unsaid in the Western tradition of metaphysics. How can deconstruction help us to untangle, demystify, transgress the limits and limitations of the aporia of the death of philosophy and resolve the question of its question, and of its right, its institution, as well as who has the right and responsibility to respond to it?